Pengetahuan Lokal sebagai Reaksi Komunitas dalam Manajemen Bencana : (Studi Etnografi Warga Brau, Batu, Indonesia) - Kristiono Dwi Susilo, Rachmad; Arrozy, Ahmad (Sodality: Jurnal Sosiologi Pedesaan, 2020)
This study aims to undertake a series of arguments to reinforce the role of local knowledge in facing environmental disaster risk. The symptoms of environmental change are observed from actor perspectives which are relatively close to the events of natural disasters so that they are recorded in their cultural expression. Ethnographic methods were chosen to illustrate how the actions are carried out and who are the actors involved in anticipating environmental disasters. Data were obtained from five informants, namely one key informant, two main informants, and two supporting informants. The results of this study indicate that: (1) local knowledge contributes positively to encourage actors to do best practices to anticipate environmental disasters, (2) there are social effects in the form of rescuing villagers or residents from natural disasters physically, mentally and spiritually.